Perceptions of Meat Alternatives Among Adolescents in Korea - Bo-young Lyum; Su-ryeon Han; Minseo Choi; Mi-kyeong Choi (Clinical nutrition research, 2025)
We investigated adolescents’ perceptions of meat alternatives and examined the relationships among their views on various types of these alternatives. A survey was conducted with 372 middle and high school students, focusing on their perceptions of 3 categories of meat alternatives: plant-based meats, edible insects, and cultured meats. The relationships among these perceptions were subsequently analyzed. Overall, 77.4% of respondents were aware of meat alternatives, and 38.7% reported having consumed them. Perception levels differed by category, with plant-based meats receiving the highest scores, followed by cultured meats and edible insects. Notably, perceptions across the different categories of meat alternatives were significantly correlated. These findings suggest that increasing awareness about meat alternatives―particularly through education―may help promote sustainable and healthy eating behaviors among adolescents.